Mastering Azure Virtual Desktop a practical guide to designing, implementing, and managing Azure Virtual Desktop environments - Mangan, Ryan; McLoughlin, Neil; Meurer, Marcel (Packt Publishing Ltd., 2024)
Acquire in-depth knowledge for designing, building, and supporting Azure Virtual Desktop environments with the updated second edition of Mastering Azure Virtual Desktop. With content aligned with exam objectives, this book will help you ace the Microsoft AZ-140 exam. This book starts with an introduction to Azure Virtual Desktop before delving into the intricacies of planning and architecting its infrastructure. As you progress, you'll learn about the implementation process, with an emphasis on best practices and effective strategies. You'll explore key areas such as managing and controlling access, advanced monitoring with the new Azure Monitoring Agent, and advanced application deployment. You'll also gain hands-on experience with essential features like the MSIX app attach, enhancing user experience and operational efficiency. Beyond advancing your skills, this book is a crucial resource for those preparing for the Microsoft Certified: Azure Virtual Desktop Specialty certification. By the end of this book, you'll have a thorough understanding of the Azure Virtual Desktop environment, from design to implementation.
Includes bibliographical references and index
Keywords: Microsoft Azure (Computing platform); Virtual computer systems; Microsoft Azure (Plateforme informatique); Systèmes virtuels (Informatique)